2022
DOI: 10.20525/ijrbs.v10i8.1450
|View full text |Cite
|
Sign up to set email alerts
|

The effect of financial knowledge on firm performance

Abstract: This research aims to know the effect of financial knowledge on firm performance; the role of financial behavior and access to finance as mediation and the role of financial risk attitude as moderation. The object of this research is the owner of small-medium enterprises, sector food and beverage in Malang. Data collection was carried out using a questionnaire of 150 respondents. Data analysis of this research uses partial least square (PLS). The finding indicates that financial knowledge has a positive and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…They refer to the ability to understand and use the company's financial statements to calculate fundamental financial ratios that allow the business to be adequately evaluated and managed. In this way, the entrepreneur's financial literacy is an important determinant of a company's performance, and various research around the world has demonstrated the relationship between these variables (Wati et al 2021;Augustin et al 2020;Agyapong and Attram 2019;Engström and McKelvie 2017).…”
Section: Financial Literacy and Company Performancementioning
confidence: 99%
“…They refer to the ability to understand and use the company's financial statements to calculate fundamental financial ratios that allow the business to be adequately evaluated and managed. In this way, the entrepreneur's financial literacy is an important determinant of a company's performance, and various research around the world has demonstrated the relationship between these variables (Wati et al 2021;Augustin et al 2020;Agyapong and Attram 2019;Engström and McKelvie 2017).…”
Section: Financial Literacy and Company Performancementioning
confidence: 99%
“…Ye & Kulathunga, (2019) Financial risk attitude is the extent to which companies are willing to pursue risky financial resource opportunities in ventures with unknown outcomes. Wati et al, (2021) explain that financial risk attitude can be said to be the tendency of individual attitudes in making risky or risk-averse decisions in possible outcomes and situation uncertainty. Risk-averse companies will receive low returns in exchange for less risk exposure, while entrepreneurs who are willing to take higher risks will compensate with high expected returns.…”
Section: Financial Risk Attitudesmentioning
confidence: 99%
“…Financial inclusion is a key factor in supporting economic growth, especially by optimizing the contribution of the financial sector and expanding access to financial services for the public. Commercial entities such as MSMEs, requires capital assistance so that they can grow their businesses and contribute to their performance (Chuc et al, 2022;Malagueño, Lopez-Valeiras, & Gomez-Conde, 2018;Mujanah, Ratnawati, & Kusmaningtyas, 2019;Nuryakin, Widowati, & Fatmawati, 2018;Tram, Lai, & Nguyen, 2023;Wati, Sumiati, & Andarwati, 2021). The existence of a research deficit creates gaps or opportunities for researchers to conduct research or further investigate the relationship between financial literacy, fintech, and financial inclusion, which has an impact on the performance of small and medium enterprises.…”
Section: Introductionmentioning
confidence: 99%